Activating Energy Transfer Tunnels by Tuning Local Electronegativity of Conjugated Polymeric Backbone for High‐Efficiency OLEDs with Low Efficiency Roll‐Off. (15th February 2022) - Zhao, Zhennan; Liu, Yuchao; Hua, Lei; Yan, Shouke; Ren, Zhongjie
Abstract: Thermally activated delayed fluorescence (TADF) conjugated polymers are attractive for display and illumination applications owing to their excellent device performance and convenient device fabrication. However, conjugated polymers frequently encounter insufficient energy transfer from hosts to TADF units, lowering device performance. Herein, a strategy for improving light‐emitting performances through adjusting the local electronegativity of the polymeric backbones by inserting electron‐withdrawing atoms and activating energy transmission channels is proposed. Meanwhile, strongly electronegative atoms also affect the charge‐transfer natures (CT) of TADF polymers and minimize the energy difference between the lowest singlet and triplet states, leading to a rapid reverse intersystem crossing process through the vibronic coupling between 1 CT and 3 CT with extremely close energy levels. The produced TADF polymer, pBP‐PXZ, can achieve an external quantum efficiency (EQE) of 23.11%, exhibiting no roll‐off when the luminance is less than 200 cd m −2 whereas only a 3% EQE decrease at 500 cd m −2 . The EQE can even maintain above 19% under 1000 cd m −2, which is the highest efficiency among TADF polymer‐based organic light‐emitting diodes (OLEDs) under high luminance. The study provides a new perspective for designing high‐performance OLEDs materials. Abstract : Strongly electronegative atoms would activate energy transfer tunnels of conjugated polymeric backbones and thus enhance the energy transfer process from the hosts in the backbones to the thermally activated delayed fluorescence units. A simple side chain conjugated polymer with oxygen atoms inserted into the polymeric backbones is reported as a high‐performance OLEDs material with low efficiency roll‐off.